Preliminary Results Regarding Sleep in a Zebrafish Model of Autism Spectrum Disorder - Madalina Andreea Robea; Alin Ciobica; Alexandrina-Stefania Curpan; Gabriel Plavan; Stefan Strungaru; Radu Lefter; Mircea Nicoara (Brain Sciences, 2021)
Autism spectrum disorder (ASD) is one of the most salient developmental neurological diseases and remarkable similarities have been found between humans and model animals of ASD. A common method of inducing ASD in zebrafish is by administrating valproic acid (VPA), which is an antiepileptic drug that is strongly linked with developmental defects in children. In the present study we replicated and extended the findings of VPA on social behavior in zebrafish by adding several sleep observations. Juvenile zebrafish manifested hyperactivity and an increase in ASD-like social behaviors but, interestingly, only exhibited minimal alterations in sleep. Our study confirmed that VPA can generate specific ASD symptoms, indicating that the zebrafish is an alternative model in this field of research.